2001
DOI: 10.1128/cdli.8.5.997-1002.2001
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Antibodies to Microorganisms Known To Cause Arterial and Myocardial Damage in Patients with or without Coronary Stenosis

Abstract: Infections are assumed to play a role in coronary artery disease (CAD) and cardiomyopathies. It is unknown whether the seroprevalence of antibodies to these microorganisms is higher in patients with than without CAD. The seroprevalence of antibodies to Bartonella henselae, Borrelia burgdorferi, Chlamydia pneumoniae, Coxiella burnetii, Helicobacter pylori, human granulocytic Ehrlichia, Leptospira, Rickettsia conorii, and Treponema pallidum was assessed prospectively in patients with exertional dyspnea or angina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
7
2
Order By: Relevance
“…Moreover, 6 of 8 (75%) Bartonella seroreactive or PCR positive dogs had evidence of cardiac disease. Myocardial injury has been reported in infective endocarditis in dogs [11,32] and in human bartonellosis [25,47]. Surprisingly, there was not echocardiographic evidence of endocarditis in any dog in this study.…”
Section: Brazil-1;contrasting
confidence: 54%
“…Moreover, 6 of 8 (75%) Bartonella seroreactive or PCR positive dogs had evidence of cardiac disease. Myocardial injury has been reported in infective endocarditis in dogs [11,32] and in human bartonellosis [25,47]. Surprisingly, there was not echocardiographic evidence of endocarditis in any dog in this study.…”
Section: Brazil-1;contrasting
confidence: 54%
“…While these results are similar to some previously published studies [5,8,[16][17][18][19][20], it is not concordant with others [9,[21][22][23][24][25][26][27][28]. It is worth repeating that this discrepancy seems to have arisen from the previously various methods of evaluating H.pylori infection and atherosclerosis.…”
Section: Discussioncontrasting
confidence: 42%
“…11:106, 2001), whereas others did not (16,26,29,47,77). Further studies found an association, adequately explained by the much stronger association of H. pylori infection with age, male gender, and social class, which are linked with coronary heart disease (68,87,95). In a study of socioeconomically homogeneous men, controlled for age and smoking, limited evidence of association between H. pylori exposure and risk for future myocardial infarction was found (82).…”
Section: Infectious Pathogens (I) Helicobacter Pylorimentioning
confidence: 95%
“…Dis. 11:106), whereas others did not (16,19,39,41,42,61,63,83,95,100). The main explanations for these controversial findings are that the studies were done in different populations, used different criteria for controls, were adjusted for potential confounders to different degrees, and were, therefore, prone to different biases.…”
Section: Infectious Pathogens (I) Helicobacter Pylorimentioning
confidence: 99%